Examining Survival Outcomes of 852 Women With Advanced Ovarian Cancer: A Multi-institutional Cohort Study. Issue 5 (June 2018) - May, Taymaa; Altman, Alon; McGee, Jacob; Lu, Lin; Xu, Wei; Lane, Kelly; Ghatage, Prafull; Rosen, Barry
Abstract : Introduction: This study examines patterns of clinical practice in the management of women with advanced high-grade serous ovarian carcinoma (HGSC). Methods: A total of 852 patients with advanced HGSC were included in this retrospective cohort analysis. Patients underwent primary cytoreductive surgery (PCS) or neoadjuvant chemotherapy (NACT). Wilcoxon rank-sum test and χ 2 test were applied. Univariate- and multivariate-analyses were performed, and survival outcomes were measured using Kaplan–Meier curves. Results: A total of 449 (53%) of 852 patients underwent PCS, and 403(47%) of 852 patients underwent NACT. The median 5-year overall survival (OS) was 3.89 in PCS and 2.48 in NACT. Patients with 0 mm residual had OS of 4.66, compared with 1- to 9-mm residual (OS = 2.80) and 10-mm residual or longer (OS = 2.50). The survival advantage harbored by the extent of surgical cytoreduction was more pronounced in PCS compared with NACT ( P < 0.001). Patients who had PCS with 1- to 9-mm residual had similar OS to NACT patients with 0-mm residual ( P = 0.17) and superior OS to NACT with 1- to 9-mm residual ( P < 0.001). Conclusions: In this multicenter study, 53% of women with advanced HGSC seen by a gynecologic oncologist were selected for PCS. Survival was longer in patients who underwent PCS than patients who underwent NACT. Within each group, survival was highest in those who had complete cytoreduction to 0-mm residual disease. We believe all patients with advanced HGSC should be assessed by a gynecologic oncologist for the feasibility of surgical resection. Primary cytoreductive surgery should be the favorable treatment modality with the goal of complete resection to 0 mm residual disease. Importantly, if 0 mm residual is not feasible, PCS to a residual of 1 to 9 mm should be attempted given the survival advantage in this group over patients who were treated with NACT. Abstract : Supplemental digital content is available in the text.